STUDI PENGOLAHAN AIR BUANGAN DOMESTIK MENGGUNAKAN DIGESTER ANAEROBIK SATU TAHAP DAN DUA TAHAP - Tamaria Kesia Hutasoit, Halimatuddahliana, Amir Husin (Universitas Sumatera Utara, 2018)
This research provides an analyzed performance of one and two-stage anaerobic digestion processes. One-stage and two-stage analyzed, individual, from substrate degradation, microbiological, metabolite and biogas production. First, the research initiated by acclimatization in a neutral condition and acid condition. Both one (R1) and two-stage (R2) digesters filled up with domestic wastewater. Into the digesters, it added cow dung as inoculums. pH in R1 maintained at pH 7 for 40 days and pH 5.5 in two-stage anaerobic: first stage (R2-1) for two days. After that, the mixture added with inoculums and then adjusted at pH 7 for the second stage (R2-2) for 38 days. The results showed that the substrate removal efficiency of two-phase is higher one-phase. The highest metabolite production obtained at R2-1: the 2nd day.